2011
DOI: 10.1002/cctc.201100197
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective Catalytic N‐Alkylation of Amines with Alcohols in Water

Abstract: Getting fresh with iridium: Water is the solvent of choice in the N‐alkylation of amines with iridium catalysts. Numerous secondary and tertiary amines can be assembled with excellent yields and chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…With water-soluble and air-stable iridium-amine complex [Cp*Ir(NH 3 ) 3 ]I 2 (102) as the catalyst, various secondary and tertiary amines were synthesized by the N-alkylation reactions of theoretical equivalents of amines and alcohols in water without a base under air. 117,118 In this case, versatile alcohols and amines were employed to undergo the BH-type reactions, giving the target higher-order amine products (eqn (37)). (37) N-Alkylation of poor nucleophilic sulfonamides with alcohols was performed in water by means of a water-soluble iridium complex {Cp*Ir[6,6 0 -(OH) 2 -bpy](H 2 O)}(OTf) 2 .…”
Section: Substitution Of Alcohols By N-nucleophiles In the Aqueous Phasementioning
confidence: 99%
“…With water-soluble and air-stable iridium-amine complex [Cp*Ir(NH 3 ) 3 ]I 2 (102) as the catalyst, various secondary and tertiary amines were synthesized by the N-alkylation reactions of theoretical equivalents of amines and alcohols in water without a base under air. 117,118 In this case, versatile alcohols and amines were employed to undergo the BH-type reactions, giving the target higher-order amine products (eqn (37)). (37) N-Alkylation of poor nucleophilic sulfonamides with alcohols was performed in water by means of a water-soluble iridium complex {Cp*Ir[6,6 0 -(OH) 2 -bpy](H 2 O)}(OTf) 2 .…”
Section: Substitution Of Alcohols By N-nucleophiles In the Aqueous Phasementioning
confidence: 99%
“…This catalysis has attracted a great deal of attention in recent years as an environmentally benign process of synthesizing amines, which produces water as the sole byproduct . While both heterogeneous and homogeneous catalysts have been known to promote the reaction, ruthenium and iridium complexes have constituted a vast majority of the homogeneous catalysts because of their relatively high catalytic performance with high product selectivity . We have found that complex 1 exhibits catalytic activity comparable to that of those complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Although this result could be considered as an appreciable achievement in comparison with the original discovery, from a preparative point of view, the use of tertiary amines as substrates is limited by their low availability and by the expected different selectivity in the transferred group when non-symmetrical tertiary amines are employed. [19] As exemplified in Scheme 2, a possible additional interesting aspect may be the use of o-phenylenediamine 3 in conjunction with Pd/C to transform a tertiary amine (such as 11) into a secondary one (14), a process that is still difficult to carry out. [26] Supported by the results of Table 1, o-phenylenediamine 3 was subjected to cyclization using dibutylamine (15) and even butylamine (16) obtaining a satisfactory conversion into 2-propylbenzimidazole 12 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…The oxidized form (sometimes unstable by itself) is further treated with other reagents and the produced hydrogen molecule is charged on the acceptor compound (generally organic) in order to shift the reaction and regenerate the catalyst. Catalytic amination of alcohols, [13] synthesis of tertiary amines, [14] imines or amides [15,16] are the most explored transformations and homogeneous transition metals have been widely employed as the catalysts. Although in some cases acceptable TON values have been reached, [17] the catalysts are often expensive {e.g., (Cp* 4 A C H T U N G T R E N N U N G (m-H)} and require the use of ligands, introducing additional troubles for product isolation.…”
Section: Introductionmentioning
confidence: 99%